Investigating the dynamics of cultural mutations in local medicinal plant use in NE Brazil - Dantas, Janilo Italo M.; Nascimento, André Luiz B.; Silva, Taline Cristina; Albuquerque, Ulysses Paulino; Araújo, Elcida de Lima (Ethnobotany Research and Applications, 2024)
Background: According to cultural evolution theory (CE), the transmission of cultural information can be subjected to "cultural mutations" (random alteration of information). Cultural mutations can have implications for human culture. However, the contributing factors to the increased/decreased establishment of these processes in local medical systems remain unclear. Thus, we tested the following hypotheses: H1: more conservative transmission modes (vertical transmission) are less prone to cultural mutation; H2: knowledge sharing about a medicinal plant influences the occurrence of cultural mutations in local medical systems; and H3: information on versatile medicinal plants (plants used to treat various ailments) is more likely to undergo cultural mutation in local medical systems. Methods: To test our hypotheses, we conducted a case study in the Lagoa do Junco community, Santana do Ipanema municipality, Alagoas. The data were collected through semistructured interviews with 120 individuals older than 18 years. Analyses utilized a generalized linear model (GLM) with the binomial and Poisson families. Results: We found a lower cultural mutation rate for more conservative transmission modes (p<0.01). Information about more widely shared medicinal plants was more prone to cultural mutations (p<0.001). Versatile medicinal plants are more susceptible to cultural mutations. Conclusions: Less conservative cultural transmission modes promote greater variation in plant-based medicinal systems. Factors such as information sharing and plant versatility, though important in local medical systems, may have implications for human culture, as exemplified by maladaptive cultural traits, and need assessment in future studies. Keywords: Cultural evolution, Copy errors, Ethnobotany, Medicinal plants